On the (im-)possibility of representing probability distributions as a difference of i.i.d. noise terms - Christian Ewerhart; Marco Serena (University of Zurich, Department of Economics, 2023)
A random variable is difference-form decomposable (DFD) if it may be written as the difference of two i.i.d. random terms. We show that densities of such variables exhibit a remarkable degree of structure. Specifically, a DFD density can be neither approximately uniform, nor quasiconvex, nor strictly concave. On the other hand, a DFD density need, in general, be neither unimodal nor logconcave. Regarding smoothness, we show that a compactly supported DFD density cannot be analytic and will often exhibit a kink even if its components are smooth. The analysis highlights the risks for model consistency resulting from the strategy widely adopted in the economics literature of imposing assumptions directly on a difference of noise terms rather than on its components.
Keywords: C46; C6; 330; Differences of random variables; density functions; characteristic function; uniform distribution